Household Consumption in Neoclassical Macroeconomics – Assumptions and Reality - Damyanov, Dimitar (Research Papers, 2019)
The main assumptions on which neoclassical economic theory is built and which underlie its recommendations for economic policy include the atomism and rationality in individual behaviour as well as the maximization of utility and profits. Along with several other key conditions, they also form the basis for the neoclassical theory of household consumption and saving. This paper presents several examples of deviations from these assumptions, based on the behaviour of Bulgarian households during the period 2000 – 2018. They highlight the need for a careful evaluation of prevailing conditions whenever we try to model economic dynamics and to develop and implement macroeconomic policies.